PERTUMBUHAN DAN HASIL BAWANG MERAH VARIETAS BIMA YANG DIBERI PERLAKUAN KONSENTRASI POC DARI KOTORAN SAPI DAN BEBERAPA JENIS TANAMAN - nova deviyanti lussy (Partner, 2020)
The study aimed to determine the effect and the best concentration of POC from cow feces and some of plant species on the growth and yield of organically cultivated shallots. The study was conducted from October 2018 to January 2019 in the Gardens of the Rinbesihat Applied Sciences Training Center, West Tasifeto District, Belu Regency. The design used a randomized block design (RBD) with seven treatments and four replications. The treatment were without POC; 50 ml/l POC concentration; 100 ml/l; 150 ml/l; 200 ml/l; 250 ml/l; and 300 ml/l. The dosage of POC application is 200 ml/plant given on a week after plant until a week before harvest (53 day after plant) with seven days interval of giving. The data obtained were analyzed for data variance and if there was a real effect then it was continued with the 5% of BNJ Test. The parameters observed were: plant height (cm), number of leaves, number of tillers per plant, number of tubers per plant, and fresh weight of tubers per plant (g). The results obtained were: POC given from cow feces and several types of plants had a significant effect on plant height on 2, 4, 5 week after plant, number of leaves on 2 week after plant, and the number of shallots tillers. POC given from cow dung and several types of plants with 50 ml / liter of water gave the highest growth and yield compared to other treatments, this was seen in 5 weeks after plant height which was 37.13 cm, leaf number of 5 weeks after plant for 30.56 strands, number of tillers was 2.69, and fresh weight shallot bulb of 65.76 grams. Keywords: POC, cow feces, legume, banana stem, shallot.